Synthesis, Characterization of CdZnS Thinfilms and SnS Nanoparticles - Prasanna, D. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
The replacement of CdS with its ternary alloy Cd\({}_{1-x}\)Zn\({}_{x}\)S has been attempted for improvement of the (Cd,Zn)S/Cu(In,Ga)Se\({}_{2}\) solar cell performance; this has resulted in a higher efficiency of 16.9%. Moreover, the replacement of CdS with the higher energy gap ternary Cd\({}_{1-x}\)Zn\({}_{x}\)S has also led to a decrease in window absorption loss and has resulted in an increase in the short circuit current in the solar cell. In this work, the Zn-CdS thin films were fabricated on glass substrates under optimized chemical bath conditions and its structural, surface and optical properties were investigated and the results of the optimized sample are presented and discussed. Among them, the solvent growth technique is very effective in yielding a desirable size distribution and optimization of the physical properties.\ For investigation the materials are synthesized using chemical bath deposition technique. The ternary compound CdZnS were deposited by various methods such as metal organic chemical vapor deposition (MOCVD), spray pyrolysis, vacuum evaporation, chemical bath deposition, successive ionic layer absorption and reaction (SILAR). Among these, the chemical bath deposition (CBD) method is a cost effective, simpler and more reliable method and gives the more precise possibility of obtaining films with required and suitable properties for optoelectronic applications and also applicable to large area deposition. Due to the incorporation of Zn\(^{2+}\) in to CdS thin films enhances the open-circuit voltage and short-circuit current in hetero-junction devices which results the decrease in the window absorption losses. The growth of SnS materials in single crystal, polycrystal-line, thin films and other forms has been carried out by various well known chemical, mechanical and physical methods.